Allergic bronchopulmonary aspergillosis in two patients with cystic fibrosis - Anadol, Deniz; Özçelik, Uğur; Kiper, Nural; Göçmen, Ayhan (The Turkish Journal of Pediatrics, 2000)
Allergic bronchopulmonary aspergillosis (ABPA) is hypersensitivity to Aspergillus fumigatus which manifests as episodic wheezing, usually refractory to bronchodilator therapy, with fixed and transient pulmonary infiltrates, central bronchiectasis, blood eosinophilia, elevated serum IgE level, immediate skin reactivity to an A. fumigatus antigen and precipitating antibodies to A. fumigatus. It is an unusual complication of asthma and cystic fibrosis (CF). We present two cystic fibrosis patients with ABPA treated successfully with prednisone and, in Case 1 also with itraconazole. The physician should be alert to the possibility of ABPA whenever CF patients present with the new infiltrates, high serum total IgE and other positive parameters of A. fumigatus sensitization. Treatment with systemic steroids should be started in order to prevent irreversible lung damage.
Keywords: allergic bronchopulmonary aspergillosis; cystic fibrosis